Hubungan Risiko Perusahaan dan Risiko Pasar serta Pengaruhnya pada Tingkat Diversifikasi Portofolio Saham - Kusbiantono, Kusbiantono (Journal the Winners: Economics, Business, Management, and Information System Journal, 2002)
This research objectives is to know empirically the connection between market risk and company risk on individual stock and portfolio stock, also the effect on stock diversification on Jakarta Stock Exchange. The result is there is correlation between market risk and company risk on individual stock and portfolio stock. Stock portfolio that form from stock with low beta score have smaller company risk compare to stock portfolio that form from stock with high beta score. The bigger number of stock in portfolio, the better diversification level on that portfolio. Â